Potential of shallot peels as a daily antioxidant supplement against cigarette smoke-induced lung damage - Helianti, Dina; Dewi, Rosita; Munawaroh, Ayu; Rachmania, Sheilla; Maulana, Aditha Satria; Abrori, Cholis; Sumadi (Faculty of Medicine, Universitas Islam Indonesia, 2024)
Background: Cigarette smoking damages the alveoli through oxidative stress. Shallot peels containing flavonoids, especially quercetin, potentially serve as a daily antioxidant supplement to impede lung tissue damage induced by cigarette smoke. However, the maximum effective dose is yet to be determined. Objective: This research was designed to establish the maximum effective dose of shallot peel infusion (SPI) to prevent oxidative stress and histopathological lung damage induced by cigarette smoke. Methods: This experimental laboratory was a posttest-only control group design. A total of 24 male Rattus norvegicus Wistar strain, were allocated into 6 groups: a control group and 5 SPI-treated groups. All rats were exposed to 2 cigarettes/day and were treated for 28 days with aquabidest and different doses of SPI (0 mg/kgBW, 125 mg/kgBW, 250 mg/kgBW, 500 mg/kgBW, 1,000 mg/kgBW, and 2,000 mg/kgBW). The level of oxidative stress in serum was measured malondialdehyde (MDA) level with ELISA, and histopathological lung damage was estimated using the lung histopathological damage scoring method assessing inflammatory cells, alveolus lumen and inter-alveoli junction.Results: The quadratic regression analysis revealed the maximum effective dose of SPI to prevent oxidative stress and lung damage were 1,435 mg/kgBW and 1,206 mg/kgBW, respectively. In the histopathological examination of the lungs, the administration of SPI up to a dose of 1206 mg/kg BW prevents the inflammatory process caused by cigarette smoke, which is indicated by the number of inflammatory cells, the thickness of the alveolar septum, and the increasingly normal shape of the alveolar lumen.Conclusion: SPI doses of less than 1,206 mg/kgBW are safe and effective daily antioxidant supplements in rats exposed to cigarette smoke and have the potential to be further studied for application in humans.